Negotiations Between Pt. Kencana Katara Kewala (K3) And Palm Oil Toke In Ketahun Sub-District, North Bengkulu District - Adi Mirwan; Sari, Sapta; Putra, Dilmai (Social Sciences Journal, 2025)
Negotiation is basically an exchange of information that aims to reach an agreement between two or more parties, so the ability to convey messages clearly and understand the other party's point of view is very important. This study aims to determine the negotiations between PT Kencana Katara Kewala (K3) and Palm Oil Toke in Ketahun District, North Bengkulu Regency. This research is a qualitative research. Based on the theory used is the theory of negotiation elements according to Achmad Romsan. The results of this study found that, first, the relationship between PT Kencana Katara Kelawa (K3) and the palm oil toke was well established. Second, interests, in conveying the interests of both parties negotiate on the basis of mutual interests. Third, options, PT Kencana Katara Kewala (K3) proposes price options based on quantity, price options, payment terms, price offers based on palm quality and so on. Fourth, options, PT Kencana Katara Kewala (K3) provides options regarding palm oil prices to palm oil toke by paying attention to several things such as market research, compiling price options, preparing proposals, presenting to toke, discussion and negotiation, offering explanations, determining agreements, follow-up. Kelima kriteria, kriteria yang dirancang untuk membantu negosiasi berjalan dengan baik dalam wawancara meliputi persiapan yang matang, komunikasi yang efektif, fleksibilitas, fokus pada solusi bersama, dan kejelasan perjanjian. Keenam komunikasi, komunikasi yang berlangsung pada saat negosiasi antara PT. Kencana Katara Kewala (K3) dengan toke sawit seperti mendiskusikan opsi yang ditawarkan dengan fokus utamanya adalah transparansi. Ketujuh Komitmen, Kesepakatan antara PT. Kencana Katara Kewala (K3) dan Toke Sawit didasarkan pada diskusi yang jelas tentang kebutuhan, harga dan kualitas sawit. Dengan demikian, unsur-unsur negosiasi dapat menjadi langkah efektif dalam melakukan negosiasi.